The Perfect Storm: A Rheumatologist's Point of View on COVID-19 Infection - Kobak, Senol (Current Rheumatology Reviews, 2021)
The new coronavirus infection (Covid-19) is a pandemic that has affected the whole world and progresses with high morbidity and mortality. It has a high contagion rate and a course capable of rapid lung involvement with severe acute respiratory distress syndrome (ARDS) and pulmonary insufficiency. A severe clinical picture develops as a result of a “perfect cytokine storm” which results from possible immunological mechanisms triggered by the viral infection. Immune system dysregulation and possible autoinflammatory and autoimmune mechanisms are responsible for a higher amount of cytokines release from immune cells. Although no clear treatment of Covid-19 infection has emerged yet, it is argued that some disease-modifying anti-rheumatic drugs (DMARDs) may be effective in addition to anti-viral treatments. These drugs (anti-malarial drugs, colchicum dispert, biologics) have been well known to rheumatologists for years because they are used in the treatment of many inflammatory rheumatologic diseases. Another important issue is whether DMARDs, which can cause severe immunosuppression, pose a risk for Covid-19 infection and whether they have been discontinued beforehand. Although there are insufficient data on this subject, considering the risk of disease reactivation, patients may continue their DMARDs treatment under the supervision of a rheumatologist. In this article, the possible immunological mechanisms in the pathogenesis of Covid-19 infection and the efficacy and safety of various DMARDs used in the treatment are discussed from a rheumatologist’s perspective in the light of recent literature data.
Keywords: infection